Preventive effect of a high fluoride toothpaste and arginine-carbonate toothpaste on dentinal tubules exposure followed by acid challenge: a dentine permeability evaluation - Pinto, Shelon Cristina (2014)
Background: Considering the current high use of high fluoride toothpastes, the aim of the study was to quantify alterations in the root dentine permeability submitted to treatment with a high fluoride toothpaste and 8% arginine, calcium carbonate, sodium monofluorophosphate toothpaste as a preventive treatment for dentinal tubules exposure followed by acid challenge. Methods: Thirty-third molars were sectioned below the cementoenamel. The root segments were connected to a hydraulic pressure apparatus to measure dentine permeability after the following sequential steps (n = 10 per group): I) Baseline; II) treatment with phosphoric acid for 30 s (maximum permeability); III) Toothbrushing (1 min) according to the experimental groups (G1- control; G2- 5000 ppm fluoride toothpaste; G3- 8% arginine-calcium carbonate toothpaste); IV) acid challenge for 5 min (orange juice). The data were converted into percentage, considering stage II as 100%. Results: The results have shown a statistically significant decreasing on dentine permeability after treatment with toothpaste (Friedman test and Dunn’s post hoc test). Comparison among groups demonstrated a high increasing on dentine permeability when acid challenge was performed after toothbrushing with distilled water (control group) (Kruskal-Wallis and Dunn’s post hoc test). Conclusion: The toothpaste treatment may provide sufficient resistance on dentine surface, preventing dentinal tubules exposure after acid challenge.